ANALISIS PERBANDINGAN USAHATANI PADI SISTEM TANAM JAJAR LEGOWO DENGAN SISTEM TEGEL DI KECAMATAN SEPUTIH MATARAM KABUPATEN LAMPUNG TENGAH - Ayu Lia Permata; Sudarma Widjaya; Achdiansyah Soelaiman (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2017)
The study aims to determine  comparison of cost structure of rice farming with’ jajar legowo’ and ‘tege’l planting systems and comparison of  income of farmers applying’ jajar legowo’ and ‘tegel’ systems in Seputih Mataram Sub-District of Central Lampung Regency. The study used a survey method. The  location is determined  purposively where ‘jajar legowo and tegel’ planting systems are implemented and it has the highest rice production in Central Lampung Regency.. Total samples are 30 farmers chosen randomly. This study was conducted in August 2015 to May 2016. This research uses ratio analysis. The results showed that the production  cost  of ‘jajar legowo’  planting system was higher than that of ‘tegel’ system especially  pesticide and labor costs.  The rice farming income with ‘jajar legowo’ was bigger than ‘tegel’ system.                                                                                                                                               Key words : comperative income, ‘ jajar legowo’,’ tegel’